Evaluation of alcohol outlet density and its relation with violence - Laranjeira Ronaldo; Hinkly David (Universidade de São Paulo, 2002)
OBJECTIVES: The current study set out to investigate alcohol availability in a densely populated, residential area of suburban São Paulo associated with high levels of social deprivation and violence. Gun-related deaths and a heavy concentration of alcohol outlets are notable features of the area surveyed. Given the strong evidence for a link between alcohol availability and a number of alcohol-related problems, including violent crime, measures designed to reduce accessibility have become a favored choice for alcohol prevention programs in recent years. METHODS: The interviewers were 24 residents of the area who were trained for the study. It was selected an area of nineteen streets, covering a total distance of 3.7 km. A profile of each alcohol outlet available on the area was recorded. RESULTS: One hundred and seven alcohol outlets were recorded. The number of other properties in the same area was counted at 1,202. Two measures of outlet density may thus be calculated: the number of outlets per kilometer of roadway (29 outlets/km); and the proportion of all properties that sold alcohol (1 in 12). CONCLUSIONS: The results of this study is compared with others which are mainly from developed countries and shown that the area studied have the highest density of alcohol outlet density ever recorded in the medical literature. The implication of this data related to the violence of the region is discussed. By generating a profile of alcohol sales and selling points, it was hoped to gain a better understanding of alcohol access issues within the sample area. Future alcohol prevention policy would be well served by such knowledge.